Twitter as safe space for self-disclosure among Malaysian LGBTQ youths - Khadijah Mohamad Tuah,; Ummu Syafiqah Mazlan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Majority of Lesbian, Gay, Bisexual, Transgender and Queer (LGBTQ) youths in Malaysia are not able to express their sexual orientation in real life due to fear of threats and backlash from society. Thus, they turn to social media like Twitter to share their true selves and sexualities. Twitter plays an important role in helping the LGBTQ youths to reveal their true selves and finding a sense of belonging to a community that supports and encourages them and in a country like Malaysia, that is important to their mental well-being. Ten participants from the LGBTQ community gave their consent to be interviewed. This study focuses on the concept of self-disclosure between the participants and their Twitter followers. The results are organized around three primary themes. 1) The motivation includes knowledge, private life, self-acceptance, and movement and clique. 2) Reciprocity in self-disclosure from both the giving and receiving end which can be positive or negative. Under the giving end, recognition is positive whereas exclusion is negative and under the receiving end, acceptance is positive while dismissal is negative. 3) Consequences of disclosure in the forms of income that is internal gain and outcome, the external gain. It is found that the participants’ actual intentions of selfdisclosure are self-acceptance and self-actualization. They use Twitter as it is seen as a private space where they can be themselves and be safe, supporting the notion of Twitter as a safe space for LGBTQ youths.